Strand invasion by HLTF as a mechanism for template switch in fork rescue - Burkovics, Peter; Sebesta, Marek; Balogh, David; Haracska, Lajos; Krejci, Lumir (Nucleic acids research, 2014)
Stalling of replication forks at unrepaired DNA lesions can result in discontinuities opposite the damage in the newly synthesized DNA strand. Translesion synthesis or facilitating the copy from the newly synthesized strand of the sister duplex by template switching can overcome such discontinuities. During template switch, a new primer-template junction has to be formed and two mechanisms, including replication fork reversal and D-loop formation have been suggested. Genetic evidence indicates a major role for yeast Rad5 in template switch and that both Rad5 and its human orthologue, Helicase-like transcription factor (HLTF), a potential tumour suppressor can facilitate replication fork reversal. This study demonstrates the ability of HLTF and Rad5 to form a D-loop without requiring ATP binding and/or hydrolysis. We also show that this strand-pairing activity is independent of RAD51 in vitro and is not mechanistically related to that of another member of the SWI/SNF family, RAD54. In addition, the 3'-end of the invading strand in the D-loop can serve as a primer and is extended by DNA polymerase. Our data indicate that HLTF is involved in a RAD51-independent D-loop branch of template switch pathway that can promote repair of gaps formed during replication of damaged DNA.
Keywords: forkhead transkripční faktory; Templates, Genetic; replikace DNA; Saccharomyces cerevisiae Proteins; Saccharomyces cerevisiae - proteiny; poškození DNA; lidé; Nuclear Proteins; DNA vazebné proteiny; DNA-Binding Proteins; DNA Replication; Adenosine Triphosphatases; Rad51 Recombinase; Replication Protein A; DNA Damage; rekombinasa Rad51; genetické matrice; Forkhead Transcription Factors; DNA; DNA-helikasy; adenosintrifosfatasy; DNA Helicases; jaderné proteiny; Humans; replikační protein A